2001
DOI: 10.1046/j.1468-8123.2001.11002.x
|View full text |Cite
|
Sign up to set email alerts
|

FT‐IR measurements of petroleum fluid inclusions: methane, n‐alkanes and carbon dioxide quantitative analysis

Abstract: A recent advancement in petroleum geochemistry is to model fossil oil composition using microthermometric and volumetric data acquired from individual¯uid inclusion analysis. Fourier Transform Infrared (FT-IR) microspectroscopy can record compositional information related to gas (CH 4 and CO 2 ) and alkane contents of petroleum inclusions. In this study, a quantitative procedure for FT-IR microspectrometry has been developed to obtain, from individual¯uid inclusions, mol percentage concentrations of methane, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…This could only be obtained by analysis and mapping at a microscopic scale. In the last decades, advances in molecular infrared microspectrometry a b, 1998Rankin et al, 1990;Pironon et Bares, 1990, Pironon et al, 2001) allow quantitative non destructive molecular analyses to be performed in a single fluid inclusion under a microscope. The size of the FI analyzed is currently restricted to the wavelength of incident beam (20 µm) when using a conventional source such as a Globar (Barres et al,1987).…”
Section: Content the Quantitative Methods For Hydrocarbon Chain Lengtmentioning
confidence: 99%
See 3 more Smart Citations
“…This could only be obtained by analysis and mapping at a microscopic scale. In the last decades, advances in molecular infrared microspectrometry a b, 1998Rankin et al, 1990;Pironon et Bares, 1990, Pironon et al, 2001) allow quantitative non destructive molecular analyses to be performed in a single fluid inclusion under a microscope. The size of the FI analyzed is currently restricted to the wavelength of incident beam (20 µm) when using a conventional source such as a Globar (Barres et al,1987).…”
Section: Content the Quantitative Methods For Hydrocarbon Chain Lengtmentioning
confidence: 99%
“…We calculated the CH 3 /CH 2 ratio, the CO 2 and the CH 4 content (Guilhaumou et al, 1990a, Pironon et al, 2001) from the relative intensities of the absorbance spectra in the range 4000-2000 cm -1 (see details in appendix). Some uncertainties may be due to diffraction effects in the mineral matrix and associated components.…”
Section: Calculation Of Molecular Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas this technique shows promise, it is not developed to the extent where Raman spectroscopy can be used to determine the H 2 O:CO 2 ratio of a fluid in an inclusion. Fourier transform infrared (FTIR) spectroscopy of fluid inclusions has primarily been applied to the analysis of petroleum in fluid inclusions (e.g., Pironon et al 2001), but has also been shown to be useful in the analysis of aqueous-carbonic fluid inclusions (e.g., Wopenka et al 1990, Brown 1992. In this study, we present FTIR results for aqueous-carbonic inclusions with a variety of compositions and molar volumes, determined at P-T conditions in the one-phase field.…”
Section: Introductionmentioning
confidence: 99%